Devil-devil - Kent, Graeme, 1933- (New York : Soho Press, 2011)
"It's not easy being Ben Kella. As a sergeant in the Solomon Islands Police Force, as well as an aofia, a hereditary spiritual peacekeeper of the Lau people, he is viewed with distrust by both the indigenous islanders and the British colonial authorities. In the past few days he has been cursed by a magic man, stumbled across evidence of a cargo cult uprising, and failed to find an American anthropologist who had been scouring the mountains for a priceless pornographic icon. Then, at a mission station, Kella discovers an independent and rebellious young American nun, Sister Conchita, secretly trying to bury a skeleton. The unlikely pair of Kella and Conchita are forced to team up to solve a series of murders that tie into all these other strange goings-on"-- Dust jacket.
Keywords: Murder -- Investigation -- Solomon Islands -- Fiction; Criminal investigation -- Solomon Islands -- Fiction; Solomon Islands -- Fiction